Reconfigurable signal modulation in a ferroelectric tunnel field-effect transistor - Zhongyunshen Zhu; Anton E. O. Persson; Lars-Erik Wernersson (Nature Communications, 2023)
Abstract Reconfigurable transistors are an emerging device technology adding new functionalities while lowering the circuit architecture complexity. However, most investigations focus on digital applications. Here, we demonstrate a single vertical nanowire ferroelectric tunnel field-effect transistor (ferro-TFET) that can modulate an input signal with diverse modes including signal transmission, phase shift, frequency doubling, and mixing with significant suppression of undesired harmonics for reconfigurable analogue applications. We realize this by a heterostructure design in which a gate/source overlapped channel enables nearly perfect parabolic transfer characteristics with robust negative transconductance. By using a ferroelectric gate oxide, our ferro-TFET is non-volatilely reconfigurable, enabling various modes of signal modulation. The ferro-TFET shows merits of reconfigurability, reduced footprint, and low supply voltage for signal modulation. This work provides the possibility for monolithic integration of both steep-slope TFETs and reconfigurable ferro-TFETs towards high-density, energy-efficient, and multifunctional digital/analogue hybrid circuits.